Prevalence of Healed Plaque and Factors Influencing Its Characteristics Under Optical Coherence Tomography in Patients With Coronary Artery Disease: A Systematic Review, Meta-Analysis, and Meta-Regression - Feng, Xunxun; Liu, Yang; Yang, Jiaqi; Zhai, Guangyao; Zhou, Yujie; Guo, Qianyun (Frontiers in Cardiovascular Medicine, 2021)
Aims: The purpose of this study was to determine the prevalence of healed plaque and its characteristics under optical coherence tomography (OCT) through a formal systematic review, meta-analysis and meta-regression. Methods and Results: Thirteen studies were selected from MEDLINE, EMBASE, Cochrane, and online databases. The overall incidence of healed plaques was 40% (95%CI: 39-42) with 37% (95%CI: 35-39) in patients with acute coronary syndrome (ACS) and with 46% (95%CI: 43-49) in patients with stable angina pectoris (SAP). The incidence of healed plaque among culprit plaques (48%, 95%CI: 46-50) was nearly two times higher than that among non-culprit plaques (24%, 95%CI: 21-27). The incidence of thin cap fibroatheroma (TCFA), plaque rupture, microvessel, macrophage accumulation and calcification was significantly higher in the healed plaque group. Meta-regression revealed an association between smoking (P=0.033) and healed plaque rupture. Gender (P=0.047) was independently associated with macrophage accumulation and mean low-density lipoprotein cholesterol (LDL-C) was independently associated with microvessel. Conclusions: In summary, with a total incidence of 40%, the incidence of healed plaques under OCT was higher in SAP than in ACS, and higher in culprit plaques than in non-culprit plaques. Higher incidence of TCFA, plaque rupture, microvessel, macrophage accumulation, and calcification was found in the healed -plaque group. Smoking, gender, and mean LDL-C level were associated with healed-plaque characteristics.